Taxonomy and antagonistic activity of A12, a new Streptomyces strain isolated from Ugandan soil (El-Wahat Journal for Research and Studies, 2016)
A newactinobacterium strain named A12 was isolated from sandy soilfromMasaka province in Uganda. To determine its taxonomic position, a polyphasic approach was used. Strain A12 producedabundantaerial myceliumon Bennett, ISP1 and ISP2 agar media which presents long filaments with spores in spiral chains, this being a morphological characteristic of the genus Streptomyces. 16S rRNA gene sequence analysis confirmed that strain A12 belongedto the genus Streptomyces and that it’s taxonomically closest to S. samsunensis M1463Twith a percentage of similarity of 99.50%. The highest antagonistic activity was observed on ISP2 medium, against Bacillus subtilisATCC 6633, methicillin resistant Staphylococcus aureus639c and Fusariumculmorum. An interesting biological activity against these three target microorganisms was also obtained on 20 different synthetic media, each containing one sugar as thesole source of carbon. Key words: soil, Actinobacteria, Streptomyces,Taxonomy, Antagonistic potential.